Organic/inorganic hybrid pigments from flavylium cations and palygorskite - Silva, G. T. M.; Silva, C. P.; Gehlen, M. H.; Oake, J.; Bohne, C.; Quina, F. H.
Features such as color, brightness and fluorescence are extremely important in applications of pigments. Hybrid materials inspired by the ancient Maya Blue pigment are a promising alternative to improve the properties and applicability of natural and synthetic dyes. In this work, we report the preparation, photophysical properties, and stability of several fluorescent hybrid pigments based on flavylium cations (FL)adsorbed on palygorskite (PAL). Five flavylium cations were investigated, viz., the 3?,4?,7-trimethoxyflavylium (FL1), 7-hydroxy-4?-methoxy-flavylium (FL2), 7-hydroxy-4-methylflavylium (FL3), 5,7-dihydroxy-4-methylflavylium (FL4)and 7-methoxy-4-methylflavylium (FL5)cations. Only FL1 and FL2, without a methyl substituent at the 4-position that could hinder inclusion in palygorskite channels, adsorbed strongly on PAL, producing fluorescent hybrid pigments with attractive colors. The spectroscopic and fluorescence properties of the FL1/PAL and FL2/PAL hybrid pigments were characterized. The color of the adsorbed dyes was somewhat more resistant to changes in external pH, photochemical stability was maintained and the thermal lability was markedly improved in the FL/PAL hybrid pigments, pointing to flavylium cations as promising chromophores for the development of fluorescent hybrid pigments with attractive colors.
Keywords: FLUORESCENT HYBRID PIGMENTS; PALYGORSKITE; DYES; CLAYS; FLAVYLIUM CATIONS; COLOR